The Effect of Auditor Competence and Work Experience on Auditor Performance Through Human Capital Management Implementation: Evidence from the Inspectorate General of Indonesia’s Ministry of Manpower - Istianto Adi Putro; Zainul Kisman (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2026)
This study examines the effects of auditor competence and work experience on auditor performance and tests the mediating role of Human Capital Management (HCM) implementation. The context is the Inspectorate General of Indonesia’s Ministry of Manpower, where timeliness and quality of audit outputs remain strategic concerns. A quantitative explanatory design was employed using saturated sampling of 70 respondents (66 auditors and 4 supervisory officials/assistant inspectors). Data were collected through a 1–5 Likert-scale questionnaire and analyzed using PLS-SEM (SmartPLS). The measurement model met convergent validity criteria (outer loadings > 0.70; AVE > 0.50) and demonstrated strong reliability (Cronbach’s alpha 0.845–0.934; composite reliability 0.886–0.944). Structural results show that competence positively and significantly affects auditor performance (β = 0.343; p = 0.001), while work experience has no significant direct effect (β = 0.059; p = 0.673). HCM implementation significantly improves auditor performance (β = 0.529; p < 0.001) and is significantly predicted by competence (β = 0.479; p < 0.001) and work experience (β = 0.595; p < 0.001). Mediation tests confirm that HCM implementation significantly mediates the effects of competence (β = 0.253; p < 0.001) and work experience (β = 0.315; p < 0.001) on auditor performance. These findings imply that experience contributes to performance primarily when it is translated into organizational HCM practices (e.g., development, placement, and performance management).